2009
DOI: 10.1128/aem.01860-08
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Ecological Success of Staphylococcus aureus Strains Colonizing Humans

Abstract: The genetic determinants and phenotypic traits which make a Staphylococcus aureus strain a successful colonizer are largely unknown. The genetic diversity and population structure of 133 S. aureus isolates from healthy, generally risk-free adult carriers were investigated using four different typing methods: multilocus sequence typing (MLST), amplified fragment length polymorphism analysis (AFLP), double-locus sequence typing (DLST), and spa typing were compared. Carriage isolates displayed great genetic diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
74
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 37 publications
14
74
2
1
Order By: Relevance
“…As many as 86.1% of the spa types were found in fewer than four individuals, and 65.5% of the spa types were observed only in single individuals. This large diversity is consistent with previous findings for both community and clinical strains (19,29,31). Still, the three most successful strains comprised 21.0% and the three largest spa CCs (spa CC012, spa CC065, and spa CC084) 62.4% of the 1,113 S. aureus nasal isolates from healthy colonized individuals in the baseline screening.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…As many as 86.1% of the spa types were found in fewer than four individuals, and 65.5% of the spa types were observed only in single individuals. This large diversity is consistent with previous findings for both community and clinical strains (19,29,31). Still, the three most successful strains comprised 21.0% and the three largest spa CCs (spa CC012, spa CC065, and spa CC084) 62.4% of the 1,113 S. aureus nasal isolates from healthy colonized individuals in the baseline screening.…”
Section: Discussionsupporting
confidence: 79%
“…The presence of more than one spa type in nasal carriers was described previously (3,29), suggesting that single-colony sampling excludes the possibility of considering the influence of different cocolonizers. However, results from a recent study on nasal carriage indicated that strain replacement was more common than cocolonization during a 9-month period (28).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, it was also observed that persistent carriage was more common in children than adults and the pattern of carriage was observe to change in most individuals between the ages of 10 and 20 years. A number of studies have revealed that quite a large number of the human populations are at great risk of S. aureus infection with some persistently colonized while others intermittently colonized (Oliveira et al, 2002;Sakwinska et al, 2009). For instance, investigation of pig farm dominated areas for nasal colonization of MRSA between farm owners, veterinarians and their non-exposed families as well as 462 pupils revealed that 86% of farmers sampled where exposed and only 4.3% of their family members were observed to carry MRSA with similar spa types belonging to that of clonal complex CC398 found in Pigs.…”
mentioning
confidence: 99%